Advanced ceramic matrix composites for high energy X-ray generation - Khan, Amir Azam; Labbe, Jean Claude (IOP Publishing, 2011)
High energy x-ray targets are the anodes used in high performance tubes, designed to work for long operating times and at high power. Such tubes are used in computed tomography (CT) scan machines. Usually the tubes used in CT scanners have to continuously work at high temperatures and for longer scan durations in order to get maximum information during a single scan. These anodes are composed of a refractory substrate which supports a refractory metallic coating. The present work is a review of the development of a ceramic metal composite based on aluminium nitride (AlN) and molybdenum for potential application as the substrate. This composite is surface engineered by coating with tungsten, the most popular material for high energy x-ray targets. To spray metallic coatings on the surface of ceramic matrix composites dc blown arc plasma is employed. The objective is to increase the performance and the life of an x-ray tube. Aluminium nitride-molybdenum ceramic matrix composites were produced by uniaxial hotpressing mixtures of AlN and Mo powders. These composites were characterized for their mechanical, thermal, electrical and micro-structural properties. An optimized composition was selected which contained 25 vol.% of metallic phase dispersed in the AlN matrix. These composites were produced in the actual size of an anode and coated with tungsten through dc blown arc plasma spraying. The results have shown that sintering of large size anodes is possible through uniaxial pressing, using a modified sintering cycle.